A phase II trial of continuous ixazomib, thalidomide and dexamethasone for relapsed and/or refractory multiple myeloma: the Australasian Myeloma Research Consortium (AMaRC) 16‐02 trial. (15th May 2021) - Bergin, Krystal; Yuen, Flora; Wallington‐Beddoe, Craig; Kalff, Anna; Sirdesai, Shreerang; Reynolds, John; Spencer, Andrew
Summary: We evaluated the efficacy and tolerability of continuous ixazomib‐thalidomide‐dexamethasone (ITd: 4 mg, day 1, 8, 15; 100 mg daily; and 40 mg weekly). A total of 39 patients with relapsed/refractory multiple myeloma (RRMM) aged ≥18 years with one to three prior lines of therapy were enrolled from two tertiary centres in Victoria and South Australia, Australia. The overall response rate (ORR) was 56·4% with a clinical benefit rate of 71·8%. The median progression‐free survival was 13·8 months [95% confidence interval (CI) 8·2–22·2] and median overall survival was not reached. The median time to best response and duration of response was 3·7 months (95% CI 2·8–10·5) and 18·4 months (95% CI 10·2–31·0) respectively. Prior immunomodulatory drug (IMID) exposure was associated with a lower ORR (40% vs. 73·7%, P  = 0·03). Survival outcomes in patients with prior proteasome inhibitor (PI) and/or IMID exposure were similar. Patients received a median (range) of 11 (1–31) cycles of therapy and six patients (15%) remained on therapy at the time of final analysis. Grade 3/4 haematological and non‐haematological adverse events were reported in 7·7% and 20·6% of patients respectively. ITd dose reductions were required in 15·4%, 48·7% and 35·9% of patients respectively. The present study demonstrates promising effectiveness and tolerability of ITd as an affordable all‐oral PI‐IMID approach for RRMM.